1987
DOI: 10.1111/j.1476-5381.1987.tb11247.x
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamine release evoked by lithium from the perfused adrenal gland of the cat

Abstract: 1 The effect of Li on catecholamine release by cat isolated retrogradely perfused adrenal gland was investigated. Replacement of Na (1 19 mM) by Li in the Krebs solution evoked a progressive increase in the spontaneous release of catecholamines that reached a maximum within 45 min and was Cadependent. This response was specific for Li, since sucrose or choline used as osmotic substitutes for Na, failed to increase the spontaneous release of catecholamines by the adrenal gland. 2 In glands perfused with Li-Kreb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In human neuroblastoma SH-SY5Y cells and other excitable cells, it has been shown that voltagesensitive Na + channels contribute to Li + influx [30,46], but not in lymphoblastoma cells [36,51]. In bovine chromaffin cells, besides the known Li + influx pathway using voltage-sensitive Na + channels [33,52], we propose here a Ca 2 + -dependent Li + influx pathway in depolarising conditions, where Li + replaces Na + in the Na + /Ca 2 + countertransport.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In human neuroblastoma SH-SY5Y cells and other excitable cells, it has been shown that voltagesensitive Na + channels contribute to Li + influx [30,46], but not in lymphoblastoma cells [36,51]. In bovine chromaffin cells, besides the known Li + influx pathway using voltage-sensitive Na + channels [33,52], we propose here a Ca 2 + -dependent Li + influx pathway in depolarising conditions, where Li + replaces Na + in the Na + /Ca 2 + countertransport.…”
Section: Discussionmentioning
confidence: 76%
“…Cell depolarisation leads to a massive Ca 2 + entry and to a large increase of intracellular Ca 2 + concentration, which increases the activity of the Na + /Ca 2 + exchanger, known to be a high-capacity, lowaffinity mechanism of Ca 2 + efflux in chromaffin cells [47,48]. It is well known that Li + can replace Na + in the Ca 2 + influx via the Na + /Ca 2 + exchanger pathway in Li +loaded chromaffin cells [33,35] and in rat skeletal muscle cells [49], where Ca 2 + influx is counterbalanced by Li + efflux. In the present case of Li + loading of the chromaffin cells, we propose that the Na + /Ca 2 + exchanger uses the external Na + and Li + to remove intracellular Ca 2 + .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when opioids are withdrawn or naloxone is applied, the neuronal in¯ux of calcium probably becomes too elevated (Bongianni et al, 1986;Baeyens et al, 1987). On the other hand, Li leads to an increase in intracellular calcium content (Abajo et al, 1987), which consequently may attenuate the appearance of increased numbers of voltage-operated calcium channels in the brain. It is therefore not surprising that Li is able to block the development of physical dependency and analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the report that calcium channel blockers attenuated the clonidine withdrawal (Barrios et al 1993), suggests that increased calcium flux may also be involved in the clonidine withdrawal syndrome. Lithium, by increasing the intracellular calcium content (Abajo et al 1987;Branisteanu & Volle 1975), may affect the calcium flux and thus exerts its effect on clonidine withdrawal syndrome. Third, chronic lithium treatment has been reported to lower the binding sites for ligands, for example opioids (Stengaard-Pedersen & Schou 1982), dopamine (Rosenblatt et al 1980), and acetylcholine (Pestronk & Drachman 1980).…”
Section: Discussionmentioning
confidence: 99%